The Implementation of Quantum Teaching (QT) and Think Talk Write (TTW) through Lesson Study to Improve Students’ Learning Motivation - M.Eval Setiawan; Sri Endah Indriwati (Scientiae Educatia: Jurnal Pendidikan Sains, 2018)
The research was intended to improve students’ learning motivation at study and learning course for fifth semester of Biology Education. Classroom Action Research has been conducted in two cycles with four phases from each cycle. Each cycle has been done based on lesson study consisting of plan, do, and see. The data were collected using a questionnaire of students’ motivation and motivation questionnaire of the observer which were measured through aspects of attention, relevance, confidance, and statisfaction.  Then data are analyzed in quantitative descriptive. The results showed that the feasibility of learning syntax on each cycle has a constant value of 100%. The average feasibility of lesson study in cycle I and II are 98.98% and 100%. The result of the average adherence to learning syntax in cycle I and II is 100%. Based on the result of the questionnaire filled by the observer shows an increase in motivation to learn between cycle I and II by 12.6%, while the average results of the students’ motivation questionnaire showed an increase of motivation to learn by 6%. The application of learning model using Quantum Learning and Think Talk Write can boost the students’ motivation to learn.